The Influence of Customer Trust and Customer Commitment to Consumer Purchase Intention of Electronic Products - Teuku Muana REFI; JAMALI; JAMIL, Muhammad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
This research conducted to investigate the effect of customer trust and customer commitment of purchase intention consumen of electronic Banda Aceh. Respondents in this research were all consumers of electronic at Banda Aceh which amounted to 100 renspond (convinience sampling). The analysis model that used in this research was the multiple linear regression. Based on the regression results found that trust and commitment positively affect to purchase intention consumen of electronic at Banda Aceh. Partially two variables that significantly affected to purchase intention, the two variables were trust and commitment (α= 0,05).